SCIENTIFIC ANALYSIS OF RUSSIAN COLLOQUIAL SPEECH - M.Jurayeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
in this article on how many inhabitants speak Russian in the world and the potential for teaching Russian in schools. I have given examples of the widespread promotion of the Russian language as a subject in kindergartens, schools, colleges and even higher educational institutions.